Political culture and moral economy in the Huánuco, Panataguas and Huamalíes rebellion (1812) - Torres Arancivia, Eduardo (2016)
After two hundred years of the uprising in Huánuco territories there are still recurrent historiographical versions that include the rebellion in an alleged cycle of pre-emancipatory movements. Faced with these opinions, this article analyzesthe political culture of those rebels to verify that in their culture still remained beliefs and attitudes of the sixteenth and seventeenth centuries, which explain their attempt to update the social pact with the monarchy. In that sense, applyingthe model of E.P. Thompson, this work proposes that the movement of 1812 was an expression of moral economy, that is, when a state attempts a modernizing change, some sectors of the society seek to defend traditional customs and rights often based on paternalistic, religious and moral grounds.